SHARIA-BASED RESOLUTION OF JOINT PROPERTY DISPUTES IN THE FAMILY - Lenny Guspidawati; Erman Gani; Alpin Syahrin; Suja'i Sarifandi (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This study examines the mechanisms for resolving joint property disputes (gono-gini) after divorce within the family, focusing the analysis on the values ​​and principles of Islamic law (sharia). This research is motivated by the high complexity and emotional conflict in the division of joint property, which often results in losses for one party. Furthermore, this study also analyzes the compatibility between Religious Court/family mediation decisions and Islamic jurisprudence principles regarding justice, welfare, and equality of rights. The results indicate that joint property is the wealth generated and accumulated by a husband and wife during their marriage, known in Indonesian Islamic family law as joint property. This includes gifts of money, a motorcycle, or other items to a husband and wife, or property purchased by the husband and wife using their own money, or savings from the husband's and wife's salaries combined. These can all be categorized as joint property. This joint property can be tangible or intangible; tangible assets can be movable or immovable, such as securities; while intangible assets can be rights and obligations. This joint property cannot be managed or distributed without the consent of both parties. Joint property is only discussed upon divorce. While neither the Qur'an nor the Sunnah explicitly regulates this issue, the Islamic jurisprudence books from various schools of thought (mazhab) do not discuss or address it. However, within Islamic law, the issue of joint property can be viewed through the concepts of Syirkah and Mashlahah al-Mursalah. In the review of positive Indonesian law, the provisions relating to joint property are the result of collective ijtihad of Indonesian jurists and scholars in the form of making a breakthrough in the vacuum of Islamic law in dealing with joint property issues, which in its determination refers to: (1) Law Number 1 of 1974 On Marriage, (2) Indonesian Civil Code, (3) Compilation of Islamic Law (KHI). In Law Number 1 of 1974 concerning Marriage, articles 35, 36, 37, it is explained that if a divorce occurs and there is a dispute regarding joint property, it will be resolved according to Islamic law for married couples who are Muslim and for married couples who are non Muslim, the settlement will be according to the Indonesian Civil Code.